It's Not Whether You Win or Lose, It's How You Place the Blame: Shifting Perceptions of Recreancy in the Context of the Deepwater Horizon Oil Spill1. (24th February 2016) - Cope, Michael R.; Slack, Tim; Blanchard, Troy C.; Lee, Matthew R.
Abstract: A key theoretical concept in the study of technological disasters is "recreancy, " which refers to perception that institutional actors have failed to carry out their responsibilities in a manner that engenders societal trust. Using household survey data from the Community Oil Spill Survey (COSS) to assess recreancy in the context of the Deepwater Horizon oil spill, we analyze four waves of the COSS collected between 2010 and 2013 to explore respondents' perceptions of blame and distrust in relation to key institutional actors associated with the disaster, paying special attention to the influence of time and employment in natural resource occupations. We show that BP is clearly viewed as the principal responsible party at fault for the disaster and that the odds of blaming BP and the federal government have held relatively steady over time, while the odds of blaming state government increased over time. We find high levels of distrust of BP and the federal government, but show that odds of being distrustful of both institutional actors was significantly lower three years after the spill. Fishing households were significantly more likely to blame and be distrustful of institutional actors, a finding that is strongly consistent with theoretical expectations.